2019
DOI: 10.15252/embr.201846794
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic control of Rab family small GTP ases through BAG 6

Abstract: Rab family small GTP ases are master regulators of distinct steps of intracellular vesicle trafficking in eukaryotic cells. GDP ‐bound cytoplasmic forms of Rab proteins are prone to aggregation due to the exposure of hydrophobic groups but the machinery that determines the fate of Rab species in the cytosol has not been elucidated in detail. In this study, we find that BAG 6 ( BAT 3/Scythe) predominantly recognizes a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 93 publications
(189 reference statements)
2
39
1
Order By: Relevance
“…Rodent CHO-K1 cells reportedly possess glucose incorporation systems (Hasegawa et al, 1990;Johnson et al, 1998), and glucose transporters provide a route for the entry of glucose into CHO-K1 cells (Hasegawa et al, 1990;Kanai et al, 1993;Wei et al, 1998;Johnson et al, 1998;Bogan et al, 2001;Selvi et al, 2010). Using this cell line, we recently showed that BAG6 plays critical roles in the appropriate trafficking of Golgi/endosomal proteins (Takahashi et al, 2019). During the course of our study, we noticed that the function of BAG6 might be linked with glucose uptake events in this cell line.…”
Section: Bag6 Deficiency Induces Partial Defects In Glucose Uptake Inmentioning
confidence: 50%
See 4 more Smart Citations
“…Rodent CHO-K1 cells reportedly possess glucose incorporation systems (Hasegawa et al, 1990;Johnson et al, 1998), and glucose transporters provide a route for the entry of glucose into CHO-K1 cells (Hasegawa et al, 1990;Kanai et al, 1993;Wei et al, 1998;Johnson et al, 1998;Bogan et al, 2001;Selvi et al, 2010). Using this cell line, we recently showed that BAG6 plays critical roles in the appropriate trafficking of Golgi/endosomal proteins (Takahashi et al, 2019). During the course of our study, we noticed that the function of BAG6 might be linked with glucose uptake events in this cell line.…”
Section: Bag6 Deficiency Induces Partial Defects In Glucose Uptake Inmentioning
confidence: 50%
“…Previously, we reported that the intracellular localization of Patched1, a GLUT4-related 12 membrane-passed sterol transporter protein, is disturbed by Rab8a depletion (Takahashi et al, 2019). Furthermore, the endosomal localization of Patched1 in HeLa cells is impaired in BAG6-depleted cells (Takahashi et al, 2019).…”
Section: Bag6 Is Required For the Insulin-stimulated Relocation Of Inmentioning
confidence: 96%
See 3 more Smart Citations